Efektifitas Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Nganjuk Periode 2016-2019 - La Ode Abdullah (Universitas Merdeka Madiun, 2021)
Optimizing tax collection requires analysis to be made to achieve the targeted tax realization. This research aims to identify the effectiveness of local tax revenue. Nganjuk Regency one of the cities Indonesia whichÂ was used as the main sample in this study. This research uses a qualitative method with the formula for analyzing the effectiveness and the analysis of the growth rate of income of each local tax in order to it can be identified the effectiveness of local taxes in Nganjuk Regency. The data collection method is done by documentation method, data used is qualitative and quantitative. The results of the application of innovations in local tax collection carried out by the Nganjuk in 2018, a Tapping Box tool to increase revenue in Hotel Tax and Restaurant Tax. There was an increase in Hotel Tax of 67.47% and Restaurant Tax of 19.96%. There were some results on using the E-SPTPD innovation. There was an increase in Entertainment Tax by 1.52%, Advertising Tax by 1.17%, Street Lighting Tax by 5.48%, and Ground Water Tax by 11.97%. The results of the application of the E-BPHTB and E-PBB innovations have provided an increase in the realization of BPHTB and PBB-P2 taxes. The increase was 50.13% for BPHTB and 17.94% for PBB-P2.Keywords: Effectiveness, Local tax,Â Original income